Computational Fluid Dynamic Analysis of Power Potential from Point Absorber Wave Energy Converters in Adipala and Pelabuhan Ratu - Zharfan Ghafara Gunawan; Zaenal Abidin; William Abednego Pardede (Department of Mechanical and Industrial Engineering, 2026)
Indonesia holds an estimated ocean wave energy potential of 17.9 GW. However, utilization remains critically low at only 0.3 MW, highlighting a significant gap between potential and deployment. This study investigates the technical feasibility of implementing point absorber-type wave energy converters (WECs) at two coastal coal-fired power plants (CFPPs) operated by PT PLN Indonesia Power: the Adipala CFPP and the Pelabuhan Ratu CFPP. A numerical simulation approach using computational fluid dynamics (CFD) was applied to assess two WEC types: swing and buoy, under site-specific wave conditions. Results show that Adipala possesses greater wave energy potential (3.17 kW/m) compared to Pelabuhan Ratu (1.1 kW/m). The buoy-type device consistently outperformed the swing type in both locations, generating average power outputs of 490.7 W and 357.1 W, respectively. The swing type yielded 119.7 W and 119.5 W. When scaled along the full 1,500-meter breakwater, the buoy-type system in Adipala offers an average power potential of 0.73 MW, peaking at 3 MW, indicating that Adipala offers superior deployment potential compared to Pelabuhan Ratu. These findings indicate strong prospects for small-scale wave energy deployment in Indonesia, especially when leveraging existing coastal infrastructure.